Analisis Kepuasan Nasabah Terhadap Layanan Mobile Banking: Studi Kasus BSI Kota Bandar Lampung - Lutfiani, Ulfa; Wulandari, Nina Ramadhani; Ruslaini, Ruslaini; Albab, Ulil (DPPM Universitas Pelita Bangsa, 2024)
This research aims to examine the influence of mobile banking service variables (Y) on customer satisfaction variables (X). The results of this study indicate that mobile banking services have an impact on customer satisfaction and can enhance customer satisfaction. Proven by the results of the correlation coefficient test or the r test through the model summary table, the r value obtained is 0.853, with a correlation value of 72.8% indicating the influence of the mobile banking service variable (Y) on customer satisfaction (X), and 27.2% influenced by other variables not explained in this study. It can be concluded that mobile banking services have a significant impact on customer satisfaction and enhance the satisfaction of customers of BSI